β-Lapachone analogs with enhanced antiproliferative activity - Ríos Luci, Carla (2012)
In this study, we describe the synthesis of a series of α- and β-lapachone containing hydroxyl or methoxyl groups on the benzene ring, by means of the selective acid promoted cyclization of the appropriate lapachol analog. The evaluation of the antiproliferative activity in human solid tumor cell lines provided 7-hydroxy-β-lapachone as lead with enhanced activity over the parent drug β-lapachone. Cell cycle studies, protein expression experiments, and reactive oxygen species analysis revealed that, similarly to β-lapachone, ROS formation and DNA damage are critical factors in the cellular toxicity of 7-hydroxy-β-lapachone.